Effect of management (ecological and conventional) on functional groups of soil microorganisms in coffee agroecosystems with different resilience to climate variability, Colombia - Garzón, Andrea Fernández; Perdomo Rivas, Laura Patricia; Avellaneda Torres, Lizeth Manuela (Acta Scientiarum. Biological Sciences, 2020)
The effect of management (ecological and conventional) on functional groups of microorganisms of soil in agroecosystems with different resilience scores reported to climate variability in Anolaima, Colombia was evaluated. Were found clustering associated with management and cellulolytic bacteria and fungi abundances. No differences found in diversity of phosphate solubilizing or nitrogen-fixing microorganisms, related to management. The diversity of microbial functional groups was affected by the climatic condition of sampling season. Management was relevant in relationships between resilience scores to climate variability and cellulolytic microorganisms; in ecological agroecosystems, biodiversity knowledge, agroecological main structure, and the participation of farmers in organizations were important